Contributions of the ischiofemoral ligament, iliofemoral ligament, and conjoined tendon to hip stability after total hip arthroplasty: A cadaveric study. Issue 12 (16th March 2022) - Tamaki, Yasuaki; Goto, Tomohiro; Iwase, Joji; Wada, Keizo; Hamada, Daisuke; Tsuruo, Yoshihiro; Sairyo, Koichi
Abstract: An adequate soft tissue balance is important in total hip arthroplasty (THA). This study assessed the contribution of the iliofemoral ligament, ischiofemoral ligament, and conjoined tendon to the range of hip rotation after THA and hip stability in response to axial traction. THA was performed in eight fresh‐frozen cadaveric specimens via an anterolateral approach using a navigation system. The ischiofemoral ligament, the medial arm of the iliofemoral ligament, and the conjoined tendon were resected in that order. The ranges of external and internal rotation and the amount of movement of the femoral head in response to axial traction were measured with the hip in 10° of extension, the neutral position, and in 10°, 30°, and 60° of flexion. Resection of the medial arm of the iliofemoral ligament significantly increased the range of external rotation in 10° of extension, the neutral position, and in 10°, 30°, and 60° of flexion. The conjoined tendon was the most important inhibitor of internal rotation from 10° of extension to 30° of flexion. Although each single element had a minor role in stabilizing the hip when axial traction was applied, resection of two or more elements significantly affected joint stability. The iliofemoral ligament and conjoined tendon are the main inhibitors of external rotation and internal rotation, respectively, when THA is performed using an anterior or anterolateral approach. Resection of two or more elements could greatly affect hip stability when axial traction is applied.